Corporate real estate: an investigation of the decision-making process for orporate relocations in Johannesburg - Mbokazi, Nelile Thembelihle (My University, 2017)
There has been a notable relocation of blue chip firms in Johannesburg. This research seeks to identify and explore the decision-making processes and the rationale behind the selection of the nodes identified as the suitable new addresses of these companies. The purpose of this study is to establish whether there is any correlation between the firms’ profile/business strategy and their nodal destination in migrating in Johannesburg. The study made use of surveys: a questionnaire was distributed via email and the Survey Monkey platform to the executives and strategists of all the selected companies. The decision-making processes were interrogated to get an intimate knowledge of how suitable nodes were identified and selected. The findings are that financial factors, location factors, property qualities, environmental factors and lease terms are all important to decisions made regarding relocation. These findings are similar to those made by other researchers in the literature. Moreover, location, accessibility, adequate parking facilities, health and safety and the quality of the building were highly prioritised pull factors
Submitted in partial fulfilment of the requirements for the MSC Property Development and Management in the School of Construction Economics and Management at the Faculty of Engineering and the Built Environment of the University of the Witwatersrand
Keywords: Business relocation--South Africa--Johannesburg; Business enterprises--South Africa--Johannesburg